PERANCANGAN ALAT PENGERING OTOMATIS GUNA OPTIMASI PRODUKSI BATIK MADURA PATENG-TENG MENGGUNAKAN METODE QUALITY FUNCTION DEPLOYMENT (QFD) PADA BATIK PATENG-TENG MADURA - Putra, Andhika Cahyono; Saputro, Andre Ridho; Kusnanto, Hadi (Universitas Muhammadiyah Tangerang, 2025)
Batik is an Indonesian cultural heritage that has been recognized by UNESCO as a humanitarian heritage for oral and intangible culture since October 2009. One type of batik that has uniqueness and high aesthetic value is the Madura Pateng-Teng Batik from Bangkalan, Madura. However, the sustainability of batik production faces big challenges due to the long production process, especially during the drying stage which still depends on weather conditions. Uneven drying can affect batik quality and extend production time, thereby reducing the efficiency and competitiveness of the batik industry. This research aims to design an automatic drying tool to optimize the production of Madura Pateng-Teng Batik by applying the Quality Function Deployment (QFD) method. This method is used to identify the needs and desires of batik craftsmen and transform these needs into appropriate technical specifications for tools. This research uses a quantitative approach by collecting data through questionnaires distributed to batik business owners in Bangkalan. The data obtained was analyzed using the House of Quality (HoQ) to determine optimal dryer specifications. The research results show that the designed automatic dryer is able to speed up the drying process, improve the quality of the final batik result, and reduce dependence on weather conditions. This tool is equipped with a temperature and time control system that can be adjusted to the type of batik cloth, and is designed with energy-saving technology to increase production efficiency. Thus, it is hoped that the application of this automatic drying tool can provide an innovative solution for Madurese Pateng-Teng Batik craftsmen, so that they can maintain production continuity and preserve the cultural heritage of typical Madurese batik.